Chatto, the life and times of an Indian anti-imperialist in Europe - Barooah, Nirode K. (Oxford University Press, 2004)
Biography of Virendranath Chattopadhyaya, 1880-1947, Indian nationalist, his political activities in Germany and contribution to Indian freedom movement.